Integration of Green Accounting to Enhance the Value Added of Micro, Small, and Medium Enterprises In Majene - Wulandari, Futri Ayu; Ariyandani, Nur; Rivai, Dian Rahmayanti; Irawati, Irawati; Ghazali, Rahmat (Department of Accounting, Faculty of Economics & Business, 2026)
This study explores the integration of green accounting as a source of value creation for Micro, Small, and Medium Enterprises (MSMEs) in Majene, West Sulawesi, Indonesia. MSME actors generally interpret green accounting as basic environmental practices—such as waste management, energy efficiency, and resource saving—rather than as formal reporting. This research addresses the gap by examining how green accounting can be understood, implemented, and transformed into added value through the perspective of value creation theory. This research collected data through in-depth interviews with four MSME owners and one government representative from the Department of Cooperatives and MSMEs in Majene. Data analysis was conducted using NVivo software and validated through source triangulation. The findings reveal that MSME actors generally interpret green accounting as basic practices, such as waste management, energy efficiency, and resource savings, rather than formal environmental reporting. Nevertheless, these practices already contribute to triple bottom line outcomes: economic (cost efficiency), social (improved reputation and customer trust), and environmental (reduced waste and cleaner surroundings). The main drivers of green accounting adoption are owner awareness and customer demand for environmentally friendly products, while barriers include limited capital, knowledge, and government support. The study concludes that integrating green accounting can strategically enhance MSME competitiveness and sustainability. The study highlights the strategic potential of green accounting to enhance MSME competitiveness and sustainability, while emphasizing the need for stronger institutional and policy support.